Literasi Membaca Puisi Guru SD - Elfia Sukma (Universitas Negeri Padang, 2019)
The purpose of this study is to describe the implementation of poetry reading literacy in elementary schools. The approach used is qualitative and quantitative. The subjects of this study were 22 Silaing Bawah Public Elementary School teachers and 22 Silaing Bawah Public Elementary School teachers. Based on the ability to read poetry obtained the average value of the results of the pre-test reading poetry evaluation of the teachers of SD Negeri 07 Silaing Bawah and SD Negeri 08 Silaing Bawah is 68.33 and is in a pretty good qualification. Whereas the average results of the reading poetry reading the evaluation of the teachers of SD Negeri 07 Silaing Bawah and SD Negeri 08 Silaing Bawah after the training was 78.58 and were in good qualifications. Thus it can be seen that the implementation of poetry reading literacy can improve the ability to read the poetry of the teachers of SD Negeri 07 Silaing Bawah and SD Negeri 08 Silaing Bawah.